Administrator and Teachers’ Perceptions of School Success in a Publicly Funded Catholic School in Ontario, Canada - Pollock, Katina (Catholic Education: A Journal of Inquiry and Practice, 2013)
School success is a complex and abstract notion. Asking questions about what is meant by school success is important, since the ways in which educators and administrators define school success tends to guide their practice, and may have implications for current and future policy initiatives. This qualitative case study explores how one publicly funded Catholic school in Ontario, Canada, conceives of school success. First, a brief historical description of publicly funded Catholic schooling in Ontario is given, followed by a short introduction of the contemporary school success discourse. Next, the methodological approach is described, leading into a detailed account of the study’s findings. Last, a comprehensive discussion follows around a particular publicly funded Catholic school’s notions of success in their local context. This study pays particular attention to the question of whether or not narrow achievement priorities from the provincial government dominate local school discourse and practices.